Implementasi Gerakan Literasi Digital Keagamaan Di Era Pandemi Covid-19 SMAN 1 Petarukan - Muftiroh, Ira; Atqia, Wirani (Edification Journal : Pendidikan Agama Islam, 2022)
Literacy is a skill to manage information properly. This research aims to describe how the implementation and benefits of the digital religious literacy movement in the pandemic era of SMAN 1 Petarukan. the method used is the method of observation, interviews and documentation. The results of the study can be concluded, 1) Implementation of the digital religious literacy movement in the pandemic era of SMAN 1 Petarukan, using google and youtube links shared by the homeroom teacher. The literacy method used is lecture and summarizing. homeroom teacher is given the authority to use one method. At SMAN 1 Petarukan the hours to carry out the religious digital literacy movement start from the 0th hour to the 1st hour. In reading literacy material for 15 minutes after that the remaining time is used for deepening based on the method used. 2) The benefits of the religious digital literacy movement in this pandemic era allow students to increase religious insight, increase students' faith, improve spiritual attitudes.